Pembentukan Karektor Pelajar Kreatif Mengikut Teori Sternberg: Suatu Analisis Kandungan dan Pembangunan Kerangka Konseptual (Sains Humanika, 2013)
Creativity is the ability to see something from a new perspective, solving problems via different solutions that are both untried and uncommon and linking the individual’s authentic and unique mental and physical awareness. Creative students are needed in society nowadays, in line with the increasingly challenging era of globalisation, as well as the rapid and rampant booming of sophisticated technology applications in our daily lives. This systematic review study which depicts discoveries from the previous journals is meant to form a conceptual skeleton on the process of forming the character of a creative student. Factors that have been identified are intelligence, knowledge, thinking styles, personality, motivation and also environment. These factors are based on the Theory Creativity of Sternberg and Amabile Creativity Component. It is essential for parents, teachers and schools to affiliate and be familiarised with these factors that have been identified as important contributors in forming the character of a creative student.
Keywords: Creativity; student character; intelligence; personality; motivation